Types and Abundance of Microplastics in Red Snapper (Lutjanus malabaricus) in Kupang Bay Waters, East Nusa Tenggara Timur: Jenis dan Kelimpahan Mikroplastik pada Ikan Kakap Merah (Lutjanus malabaricus) di Perairan Teluk Kupang, Nusa Tenggara Timur - Ngai, Maria Magdalena Mau; Toruan, Lumban Nauli Lumban; Tallo, Ismawan (Habitus Aquatica, 2024)
Microplastics are plastic particles that have a size of <5 mm. Its small size means it can be transported to all waters and biota, including fish. Sources of microplastic waste in waters include industry, agriculture and anthropogenic activities, all of which can be a source of microplastic pollution in the sea. Red Snapper (Lutjanus malabaricus) is a type of demersal fish that lives in groups at the bottom of coral or coral reefs. Red Snapper is a category of fishery products that has important economic value and is in great demand by the public. This research aims to identify the type, color, abundance and size of microplastics in Red Snapper fish. Sampling was carried out in September-October 2022 with a total of 50 fish samples studied. Identification of microplastics based on the shape, size and color of the microplastic particles. The results of the research found as many as 1,593 microplastic particles in the Red Snapper fish samples consisting of fibers, fragments, films and granules. The highest abundance of microplastics was dominated by the fiber type, namely 17.98 particles/individual in the gills and 11.66 particles/individual in the intestine. The lowest abundance of microplastics overall was in the gills with the film type being 0.28 particles/individual and the granule type being found at 0.3 particles/individual. The colors of microplastics found were white, black, red, yellow, blue, transparent and green. The highest color of microplastics found overall was dominated by white, both in the gills (52.45%) and in the intestines (48.74%), while the lowest was green which was found in the gills (0.42%) and in the intestines. intestine (0.79%). The microplastics found varied in size, namely <0.25 mm - >2 mm. The microplastics found in the two fish organs were mostly 0.50 mm - 2 mm in size. Very few microplastics measuring <0.25 mm were found, both in the intestines and gills.